Nutritional habits of people with type two diabetes mellitus - Bjelanovic, Jelena; Petric, Teodora; Pavlica, Tatjana; Rakic, Rada; Dragic, Natasa; Bijelovic, Sanja; Bjelica, Artur (Progress in Nutrition, 2020)
Background and aim of the work: Prevalence of diabetes mellitus has reached pandemic proportions.Our aims were to recognize nutritional habits of people with type two diabetes mellitus, as well as the differences in respect of gender and nutritional state. Methods: The study encompassed 50 patients from Polyclinic for Endocrinology, Diabetes and Metabolic Diseases of the Clinical Center of Vojvodina. Data were collected based on a questionnaire specially designed for this study. Results: The majority of polled patients were overweight and obese (86%), and there were no undernourished subjects. The analysis of nutritional habits showed that the intake of fatty meat and offals by males was statistically significantly higher compared to females (p=0.0229). In the group of the same nutritional state, obese subjects consumed significantly more meat products compared to those with normal nitritional status (p=0.0097). No other differences were observed. Conclusions: It is a worrying finding that the majority of subjects with type two diabetes mellitus are overweight or obese. This indicates that the energy intake is not in proportion with the energy expenditure. It is necessary to carry out more detailed studies on a larger number of subjects, which would include the amounts of foodstuffs consumed, as well as the daily energy intake, accompanied by the analysis of the level of the subjects' physical activities.